HST SHEL: Revealing Haze and Confirming Elevated Metallicity in the Warm Neptune HAT-P-26b - Lakeisha M. Ramos Rosado; David K. Sing; Natalie H. Allen; Hannah R. Wakeford; Mercedes López-Morales; Nikolay K. Nikolov; Kevin B. Stevenson; Munazza K. Alam; Thomas M. Evans-Soma (The Astronomical Journal)
We present a new and extended transmission spectrum of the warm Neptune HAT-P-26b spanning wavelengths between 0.29 and 5.0 μ m. This spectrum is derived from new HST STIS G430L observations from the PanCET program, a reanalysis of the previously published HST STIS G750L data, along with the previously published HST WFC3 IR G102 and G141 data, and the two Spitzer IRAC photometric points at 3.6 and 4.5 μ m. We present this analysis as part of the Sculpting Hubble’s Exoplanet Legacy program, where the goals are to analyze all HST archival observations of transiting exoplanets using a uniform and homogeneous reduction technique. With the new wavelength coverage, we identify a scattering slope that is weaker than Rayleigh scattering and is best-matched by models incorporating a haze-only scenario. Our retrieval analysis reveals an atmospheric metallicity of 15 ${}_{-8}^{+22}$  × solar which suggests that HAT-P-26b may have formed further out in the protoplanetary disk, in a region rich in hydrogen and helium but with fewer heavy elements, and later migrated inward. This supersolar metallicity places HAT-P-26b below the mass–metallicity trend of the solar system. Looking ahead, recent observations from JWST NIRISS/SOSS and NIRSpec/G495H will provide critical, high-precision data that extend the spectral coverage into the infrared to further constrain the atmospheric composition and structure of HAT-P-26b. These observations have the potential to confirm or refine the metallicity and haze scenario presented here, offering unprecedented insights into the atmospheric properties of warm Neptunes and the processes governing their formation and migration histories.